Inhibition of projections from the basolateral amygdala to the entorhinal cortex disrupts the acquisition of contextual fear - Sparta, Dennis R.; Smithuis, Jim; Stamatakis, Alice M.; Jennings, Joshua H.; Kantak, Pranish A.; Ung, Randall L.; Stuber, Garret D. (Frontiers in Behavioral Neuroscience, 2014)
The development of excessive fear and/or stress responses to environmental cues such as contexts associated with a traumatic event is a hallmark of post-traumatic stress disorder (PTSD). The basolateral amygdala (BLA) has been implicated as a key structure mediating contextual fear conditioning. In addition, the hippocampus has an integral role in the encoding and processing of contexts associated with strong, salient stimuli such as fear. Given that both the BLA and hippocampus play an important role in the regulation of contextual fear conditioning, examining the functional connectivity between these two structures may elucidate a role for this pathway in the development of PTSD. Here, we used optogenetic strategies to demonstrate that the BLA sends a strong glutamatergic projection to the hippocampal formation through the entorhinal cortex (EC). Next, we photoinhibited glutamatergic fibers from the BLA terminating in the EC during the acquisition or expression of contextual fear conditioning. In mice that received optical inhibition of the BLA-to-EC pathway during the acquisition session, we observed a significant decrease in freezing behavior in a context re-exposure session. In contrast, we observed no differences in freezing behavior in mice that were only photoinhibited during the context re-exposure session. These data demonstrate an important role for the BLA-to-EC glutamatergic pathway in the acquisition of contextual fear conditioning.